2021
DOI: 10.1088/1755-1315/648/1/012140
|View full text |Cite
|
Sign up to set email alerts
|

Application of liquid organic and inorganic fertilizer on growth and production of hybrid maize

Abstract: Organic fertilizers can be an alternative source of plant nutrients. The aim of experiment is to determine the effect of liquid organic and inorganic fertilizer application on hybrid mayze growth and yield. The experiment was conducted at Soppeng regency, South Sulawesi from September to December 2019. The experiment was set in Randomized Block Design with eight level of treatments and three replications. Treatments were (P1) control, (P2) inorganic fertilizer 100% recommendation, (P3) inorganic fertilizer 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Research by Kaur et al [4] proved that the mixed application of organic and inorganic fertilizers may keep maize grain yield at a relatively high level. Maintang [5] used the liquid organic fertilizer combined with the organic fertilizer and concluded that 75% of the recommended amount of grain yield is higher than other treatments. A study by Wei et al [6] observed that the combined application of organic and inorganic fertilizers has a remarkable yield-increasing effect on wheat yield.…”
Section: Related Workmentioning
confidence: 99%
“…Research by Kaur et al [4] proved that the mixed application of organic and inorganic fertilizers may keep maize grain yield at a relatively high level. Maintang [5] used the liquid organic fertilizer combined with the organic fertilizer and concluded that 75% of the recommended amount of grain yield is higher than other treatments. A study by Wei et al [6] observed that the combined application of organic and inorganic fertilizers has a remarkable yield-increasing effect on wheat yield.…”
Section: Related Workmentioning
confidence: 99%
“…Higher leaf area equals to higher photosynthesis process to help in development of the corn especially the production of corn kernel. The stem functions as translocation and transpiration of glucose and water respectively mainly to the fruits [10]. The highest recorded data for the development of the stem girth is treatment 4 (70% NPK + 30% FWF) and the lowest is treatment 3 (50% NPK+FWF) (Figure 3.).…”
Section: Figure 2 Mean Leaf Area On Different Treatmentsmentioning
confidence: 96%
“…shows the leaf area on different treatments and treatment 3 (50% NPK+FWF) recorded the highest leaf area while treatment 5 (100% FWF) has the lowest. Combination of liquid fertilizer and inorganic fertilizer resulted in higher leaf area [10]. The combine application of organic fertilizer and NPK fertilizers develops wider leaves compared to two times application of organic fertilizer alone [11].…”
Section: Figure 2 Mean Leaf Area On Different Treatmentsmentioning
confidence: 99%
“…The application of liquid NPK fertilizer which gave equal yield to the standard treatment was in the treatment of 12.5 cc L -1 and 15 cc L -1 . The results of research that conducted by Maintang et al [17] which combined liquid organic fertilizers and 75 % recommended inorganic fertilizers (15 mL per 2 L water or 7.5 mL L -1 + NPK phonska 300 kg ha -1 + urea 150 kg ha -1 ) can be the recommended dosage for optimum maize production. Another research by Arifin [18] reported that liquid NPK fertilizer 4 mL L -1 combined with 300 urea kg ha -1 + 50 SP-36 kg ha -1 was effective to increasing the yield.…”
Section: Sweet Corn Cobsmentioning
confidence: 99%